Aplikasi Android Pada Pembelajaran Seni Rupa Materi Mozaik, Kolase, Dan Montase Di Kelas IV Sekolah Dasar - Arip Nurohmat; Rosarina Giyartini; Ahmad Mulyadiprana (IKIP Siliwangi, 2021)
Abstract Knowing the needs of elementary school teachers by using the resulting product in the form of an android application to learn the differences between mosaics, collages, and montages is the goal of this research. The method used is Design Based Research (DBR), chosen because it has the aim of designing an android application for learning the fine arts of mosaic, collage, and montage materials in grade IV elementary school. The results show that teachers do not understand the difference between mosaics, collages, and montages. Through android-based applications that are made, teachers can better understand the differences between mosaics, collages, and montages anytime and anywhere because they contain understanding, materials, photos, and making videos. The final result obtained is that the android application for learning the art of mosaic, collage, and montage material can be a source of reference in carrying out learning for teachers. AbstrakMengetahui kebutuhan guru sekolah dasar dengan menggunakan produk yang dihasilkan berupa aplikasi android untuk mempelajari perbedaan mozaik, kolase, dan montase adalah tujuan dari penelititian ini. Metode yang digunakan adalah Design Based Research (DBR), dipilih karena mempunyai tujuan untuk merancang aplikasi android pada pembelajaran seni rupa materi mozaik, kolase, dan montase di kelas IV sekolah dasar. Hasil menunjukkan bahwa guru kurang memahami perbedaan antara mozaik, kolase, dan montase. Melalui aplikasi berbasis android yang dibuat, guru bisa lebih memahami perbedaan antara mozaik, kolase, dan montase kapan saja dan dimana saja karena di dalamnya terdapat pengertian, bahan-bahan, foto, dan video pembuatan. Hasil akhir yang didapat yakni aplikasi android pada pembelajaran seni rupa materi mozaik, kolase, dan montase bisa menjadi sumber referensi dalam melaksanakan pembelajaran bagi guru.